(untitled) (American Journal of Islam and Society, 2000)
The international Islamabad conference titled God, Life and Cosmos: Theistic Perspectives was held in Islamabad, November 6-9, 2000. Sponsored and organized by the Center for Theology and Natural Sciences (CTNS), Berkeley, United States, Islamic Research Institute (IRI), Islamabad, Pakistan, and International Institute of Islamic Thought (IIIT), Islamabad, Pakistan, the conference drew over fifty scholars from the fields of natural sciences and religious studies. A number of interesting papers were presented on various aspects of the relation between religion and science, and each paper was critically evaluated and responded to by a respondent. The conference commenced with the introductory remarks of Muzaffar Iqbal (National Library, Alberta, Canada) and then the keynote speech which was delivered by William Chittick, the renowned scholar of Islamic intellectual history and Ibn Arabi. Chittick’s keynote address titled “Modem Science and the Eclipse of Tawhid” focused on the sharp contrast between the Islamic concept of tuwhid (Divine unity) and the secular worldview of modem science. Drawing on the traditional distinction between the transmitted (naqli) and intellectual (uqli) sciences, Chittick emphasized the importance of intellectual sciences in confronting the challenges of the modem world. As respondent to Chittick‘s keynote paper, Hasan al-Shafi’i (President of the International Islamic University, Islamabad, Pakistan) further elaborated on the points raised by the keynote speaker. The f i t day of the conference closed with a wonderful presentation about Pakistan and its history by the son and daughter of Muzaffar Iqbal, the indefitagiable convener of the conference. The papers presented at the conference touched upon nearly all of the major aspects of the religion-science relationship: the rise of modem physical sciences and the responses of the Islamic as well as Christian worlds, philosophy of science, modem cosmology, theory of evolution and its meaning for the religious worldview, history of Islamic sciences and its ...